Peran Posyandu Dalam Upaya Penurunan Angka Stunting di Desa Sidomulyo - Muhammad Zainul Mustofa; Miftakhul Mukhlisin; Yana Suryana; Muhammad Asaduddin Kamal; Laila Nisvi Humairoh; Ananda Rahma Syiami; Atmim Nurona; Arina Manasikana; Widyastuti Widyastuti; Diya Ayu Sitta; Vina Sofia Aqlina; Afita Rizkiatul Maghfiroh; Indah Wijayanti (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2024)
Stunting remains a serious health challenge in Indonesia. This study analyzes the role of Posyandu in reducing stunting in Sidomulyo Village, Cepiring Sub-district, Kendal District. Using analytical descriptive methods, this study evaluates program implementation, challenges and outcomes. Posyandu plays an important role in child growth monitoring, nutrition counseling, supplementation, mother-child health services, early intervention, and increasing community awareness. Collaboration with various parties, including KKN-T students, strengthens these efforts. Although comprehensive, there is still room for improvement, especially in integrating technology. This holistic and collaborative approach is in line with the Indonesian government's target of reducing the stunting rate to 14%.